Switzerland : Financial Sector Assessment Program; Detailed Assessment of Observance of Financial Sector Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the detailed assessment of observance of financial sector standards and codes in Switzerland. Switzerland has a relatively unique banking sector, with a high market concentration by the two largest domestic banks. The overall assessment of the peer-review team is that Switzerland is generally in compliance with the Basel Core Principles with two exceptions where the Swiss Federal Banking Commission (SFBC) is deemed largely compliant. The two exception areas are budgetary independence and banking activities not subject to SFBC supervision.